(untitled) (Fiep Bulletin - online, 2012)
This study examined the strategies of control of discrete and cyclical movements in the Fitts’ task simulated in a virtual environment. For this, participated in the study 15 individuals of both sexes, aged between 17 and 30. The software Discrete Aiming Task v. 2.0 (Okazaki, 2007) simulated the Fitts’ task in the discrete and cyclical conditions providing the movement time (MT). Thus, the participants performed movements clicking the left mouse button on parallel bars, with a size of 2, 1, 0.5 and 0.25 inches, kept at a distance of 4 inches of each other, performing as quickly and accurately as possible. The index of difficulty (ID) in the task accomplished were 2, 3, 4 e 5 bits, respectively. Thus, we conducted eight experimental conditions, four of discrete movements (D2, D3, D4 and D5) and four of cyclical movements (C2, C3, C4 and C5). Four trials in each condition were performed in a randomized sequence. . Data were analyzed by Friedman`s ANOVA and subsequent comparisons with Wilcoxon paired test. For significance level was adopted P<0.05. There was no significant difference in the MT scores between the discrete and cyclical movements. But the increase in the ID caused an increase in the MT, showing an inverse relation between speed and accuracy. Thus, Fitts’ Law demonstrated robustness regardless of the type of movement, discrete or cyclical.